Echocardiographic examination of cardiac structure and function in elite cross trained male and female Alpine skiers. Issue 2 (1st April 1999) - George, K P; Gates, P E; Whyte, G; Fenoglio, R A; Lea, R
Abstract : OBJECTIVE: To assess cardiac structure and function in elite cross-trained male and female athletes (Alpine skiers). METHODS: Sixteen athletes (10 male, six female) and 19 healthy sedentary control subjects (12 male, seven female) volunteered to take part in the study. Basic anthropometry determined height, body mass, body surface area, and fat free mass. Cardiac dimensions and function were determined by two dimensional, M mode, and Doppler echocardiography. Absolute data and data corrected for body size (allometrically determined) were compared by two way analysis of variance and post hoc Scheffé tests. RESULTS: Absolute left ventricular internal dimension in diastole (LVIDd), septal and posterior wall thickness and left ventricular mass were larger in athletes than controls (p < 0.05) and also increased in the men (p < 0.05) compared with women (except for septal thickness in controls). An increased LVIDd, septal thickness, posterior wall thickness, and left ventricular mass in athletes persisted after correction for body size except when LVIDd was scaled by fat free mass. Cardiac dimensions did not differ between the sexes after correction for body size. All functional indices were similar between groups. CONCLUSION: There is evidence of both left ventricular chamber dilatation and wall enlargement in cross trained athletes compared with controls. Differences in absolute cardiac dimensions between the sexes were primarily due to greater body dimensions in the men.